Prevalence of nursing caries among 1-3 year old children - Ambal, Imee M.; Dayrit, Blanche Lou-Ida M.; Mabunga, Susan Y. (Adviser).
It is known for a fact that nursing caries exists but not much has been documented about it in the Philippine setting. This study aimed to determine the prevalence of nursing caries among 1-3 year old children at the Out-Patient Department of the Philippine Children's Medical Center and to describe the conditions which can be associated with nursing caries. 126 subjects were examined for nursing caries and their mother's were interviewed regarding age, sex, systemic illness, annual income, mother's awareness, feeding practices and oral hygiene of the child. A. prevalence rate of 23.8% was found and the results were subjected to Chi-square analysis at .05 level of significance. Factors such as birth order, systemic illness, educational attainment, annual income, mother's awareness, feeding habits and oral hygiene can be associated to nursing caries occurrence. This study was supported by Lamoiyan Corporation (Hapee Toothpaste).
Seminar Papaper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental caries in children